A study of factors that influence a horse owner's veterinary treatment purchasing decisions - Fahey, Shannon T., author; Hadrich, Joleen, advisor; Koontz, Stephen, committee member; Frasier, Marshall, committee member; Roman-Muniz, Noa, committee member (Colorado State University. Libraries, 2018)
There has been very little academic research done to assess and understand how horse owners make treatment decisions for their sick or injured horses. An owner's decision to treat or euthanize their sick or injured horse is not only a financial one, but an emotional one as well. This decision can also impact the veterinarian's overall welfare. The responsibility of performing euthanasia on animals has been linked to decreased job satisfaction, health problems, and increased rates of suicide among the veterinary population. There are also potential financial implications when a veterinarian has to euthanize a patient. When a veterinarian euthanizes a patient, he or she can miss out on thousands of dollars in potential future revenues from the care of that patient. For these reasons, it is imperative that veterinarians understand what influences a horse owner's decision to treat or euthanize their sick or injured horse. This study used a choice experiment and demographics survey to gather data from Colorado horse owners that was analyzed to better understand the decision-making behavior of horse owners. The main effects fractional factorial choice experiment was designed using SAS 9. In each choice set, the respondents ranked the most preferred and least preferred of three choice alternatives (Treatment A, Treatment B, and Euthanasia) they could hypothetically face if their horse was suffering from obstruction colic. The attributes for Treatment A and Treatment B were price, recovery period length, and success rate. These three attributes varied between choice alternatives and across choice sets. The only attribute for euthanasia was price, which remained constant across all choice sets. The choice experiment was included with a demographics survey and was distributed to Colorado horse owners via an anonymous Qualtrics link. The demographic questions provided further insight information about the horse owners on an individual level. The data was analyzed using a rank-ordered logit model in STATA. The first of two regressions in this study involved only the treatment attributes and a euthanasia dummy variable, and the other including treatment attributes and demographic interactions. The initial regression found that an increase in price and recovery period decreased the probability that an alternative was ranked as a more-preferred option. An increase in success rate had the opposite effect. When the demographic interactions were included in the analysis, the impact of recovery period on the ranking of an alternative was no longer statistically significant. Only certain demographic interactions were statistically significant as well. Most notably, an increase in income only had a statistically significant effect on how changes in success rate affected the ranking of an alternative. The coefficients from the initial regression were used to calculate the willingness-to-pay (WTP) values for recovery period length, success rate, and avoiding euthanasia. The WTP values suggest that horse owners most value the success rate of a treatment and are willing to pay up to $2,610 for treatment in order to avoid euthanizing their sick or injured horse. This study can serve as a baseline for future research into the veterinary spending behavior of horse, livestock, and pet owners. The results from this study can also be utilized by veterinarians to better understand their clients. With this information, veterinary clinics can make decisions that are better for their patients, their clients, and themselves.
Keywords: equine euthanasia; obstruction colic; veterinary treatment; horse owners; choice experiment; purchasing decisions